Effect of simplified and full-step surface treatments of indirect resin composite on dentin bonding stability and nanoleakage (Research, Society and Development, 2020)
The study evaluated the effect of the application of simplified or full-step surface treatments and aging times on dentin bonding stability and nanoleakage of indirect resin composite restorations. This is an in vitro study with one hundred and sixty indirect resin composite restorations (4.8 x 2.8 x 4.0 mm) produced to fill dentin preparations in bovine dentin. The specimens were divided into eight groups according to chemical treatment [No treatment; Silane; Scotchbond™ Universal adhesive (SBU); and Silane + SBU], and aging time in water [24 h and six months]. Push-out bond strength (PBS) was evaluated by a universal testing machine (1.0 mm/min), failure modes by a dissecting microscope, and nanoleakage by scanning electron microscopy. Two-way ANOVA and Tukey posthoc tests (p